Alkaline ion battery negative electrode material and preparation method and application thereof
By eroding the MAX phase and combined with frozen drying and burning treatment, the MXENE/MOS2/TIO2 composite material is prepared, which solves the problem of poor circulation stability of MOS2 negative materials, and achieves high -efficiency alkaline ion battery negative electrode materials.
Patent Information
- Application Number
- CN202411539746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
AI Technical Summary
The existing MoS2 negative electrode materials have poor cycle stability due to volume changes during circulation, which limits their application range.
Use a mixed -acid etching MAX phase material to obtain MXENE, and use frozen drying and burning treatment to prepare MXENE/MOS2/TiO2 composite materials to improve the cycle stability of the negative electrode material.
By constructing the MXene/MoS2/TiO2 ternary heterostructure, the stable cycling performance of the anode material for alkaline ion batteries was achieved, and the cycling stability and electrochemical performance of MoS2 were significantly improved.
Smart Images

Figure CN119349639A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion batteries, and in particular relates to an alkaline ion battery negative electrode material and a preparation method and application thereof. Background Art
[0002] The increasing energy demand in modern society has prompted the development of clean energy and advanced energy storage devices. Among them, rechargeable sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs) have attracted much attention due to their abundant sodium / potassium reserves and high economic efficiency, and are considered to be potential alternatives to lithium-ion batteries. However, the larger ionic radius (Na + is 0.106 nm, K + is 0.138 nm, Li + 0.076 nm) may result in slow ion transport in the negative electrode material and in Na + / K + The volume change of the active material during the insertion and extraction process is significant, which enables fast and highly reversible Na + / K + Storage is very difficult. Therefore, researchers have done a lot of work to select and design suitable SIBs and PIBs anode materials to achieve fast ion diffusion kinetics and long-term cycle stability.
[0003] Molybdenum sulfide (MoS2) is a typical two-dimensional (2D) transition metal sulfide, which has attracted much attention due to its high sodium / potassium storage capacity. At the same time, MoS2 is composed of three atomic layers (S-Mo-S), and its structure is similar to that of graphite, with a large interlayer spacing of 0.62nm, which provides a large number of ion storage sites and unobstructed ion transmission channels during the charge and discharge process. However, due to its low electrical conductivity and large volume change, MoS2 has a fast capacity decay and poor rate performance during the cycle. In order to improve the electrochemical performance of MoS2 negative electrode, researchers have done some fruitful work. Among them, titanium carbide (Ti3C2T x ) is an emerging two-dimensional material, known as MXene, which has been widely used in the field of electrochemical energy storage due to its excellent conductivity, rich surface functional groups, unique layered structure and excellent mechanical strength. Therefore, constructing MXene / MoS2 van der Waals heterostructure is an effective strategy to improve the electrochemical performance of MoS2-based anodes in SIBs and PIBs.
[0004] In the prior art, Feng Qian et al. grew MoS2 / C composite nanosheets on the surface of MXene by combining hydrothermal treatment with annealing process to form a composite structure of MoS2 / C / MXene, which showed excellent cycle performance as the negative electrode material of lithium-ion batteries at 1 A·g -1After 1000 cycles at a current density of 5.34 mAh g -1 Li Jiahui et al. prepared layered Ti3C2T by hydrothermal method. x MXene / MoS2 composite materials, in which MoS2 nanosheets are vertically fixed on the conductive MXene substrate, form a hierarchical two-dimensional structure, which has excellent performance as anode materials for potassium ion batteries. Tan Ruixuan et al. designed a 1T-2H phase MoS2@MXene composite material with a stacked multilayer heterostructure. The 1T-2H phase MoS2 is attached to the surface and interlayer of MXene in a leaf-like form, supporting the MXene layered structure, expanding the interlayer spacing, and increasing the Na+ diffusion rate. As anode materials for SIBs, at 5 A·g -1 The current density was 439.3 mAh g -1 Obviously, these studies use MXene as a matrix and load MoS2 between MXene layers and on the surface, which significantly improves the electrochemical performance of pure MoS2. However, in the above technology, the MoS2 on the surface of MXene still has a certain degree of volume expansion during the charge and discharge process. If such problems can be solved, the cycle stability of MoS2 / MXene can be further improved. Summary of the invention
[0005] The purpose of the embodiment of the present invention is to provide an alkaline ion battery negative electrode material to solve the problem that the current MoS2 negative electrode is limited in application due to poor cycle stability; The second purpose of the embodiment of the present invention is to provide a method for preparing an alkaline ion battery negative electrode material; The third purpose of the embodiment of the present invention is to provide an application of an alkaline ion battery negative electrode material.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is a method for preparing a negative electrode material for an alkaline ion battery, comprising the following steps: S1. Etching the MAX phase material using a mixed acid to obtain etched MXene; S2. Obtaining a powder containing MXene, Mo source and S source simultaneously by freeze drying; S3. Calcine the powder containing MXene, Mo source and S source to obtain a MXene / MoS2 / TiO2 composite material.
[0007] Furthermore, the mixed acid obtained in S1 is a mixture of either HCl or H2SO4 and HF; wherein the volume ratio of HF to either HCl or H2SO4 is (5~40):(10~40).
[0008] Further, during the etching process of S1, the mass volume ratio of the MAX phase material to the mixed acid is (0.5-3): (20-60) g / ml; The etching process is as follows: the mixed acid is added to the MAX phase at a rate of 0.1 g / min~0.6 g / min. After complete addition, the mixed solution is continuously stirred at 50℃~70℃ for 4 h~24 h to obtain the etched MXene mixed solution; the mixed solution is centrifuged and washed with deionized water, the centrifuge speed is maintained at 1000~4000rpm, the centrifugation time is 5~20 min, until the pH value of the supernatant is neutral, and the centrifuged precipitate MXene is collected by drying.
[0009] Furthermore, the specific process of S2 is as follows: S201, disperse the etched MXene in deionized water; add Mo source and S source containing NH4⁺, and ultrasonicate in an ultrasonic disperser for 30-120 min; S202. Freeze-dry the solution after ultrasonic dispersion at -30 ~ -70 °C for 3 ~ 12 h, and then vacuum dry it at -30 ~ 0 °C for 4 ~ 12 h to obtain a dry powder containing MXene, Mo source and S source.
[0010] Furthermore, the mass volume ratio of the etched MXene to deionized water in S201 is (0.05~0.8): (10~30) g / ml.
[0011] Furthermore, the Mo source in S201 is specifically any one of ammonium tetrathiomolybdate and ammonium molybdate, and the S source is specifically any one of thioacetamide and thiourea; the mass ratio of the MXene to the sum of the Mo source and S is (0.05~0.8):(0.1~2.0); when the Mo source is ammonium tetrathiomolybdate, the S source is not introduced.
[0012] Furthermore, the specific process of S3 is as follows: the powder containing MXene, Mo source and S source is dried and kept at 400-700°C for 0.5-5 h at a heating rate of 2-10°C / min in a nitrogen atmosphere with a flow rate of 50-200 sccm; after the reaction, a MXene / MoS2 / TiO2 composite material is obtained.
[0013] A MXene / MoS2 / TiO2 composite material prepared by the above-mentioned method for preparing alkaline ion battery negative electrode materials.
[0014] An electrode sheet using a MXene / MoS2 / TiO2 composite material as active powder and a single layer of MXene as a binder; the preparation method of the electrode sheet is as follows: S401. Pour deionized water into a polytetrafluoroethylene bottle, then add concentrated hydrochloric acid and stir to keep the concentration of HCl at 8~10.5 mol·L -1 , then slowly add LiF and stir for 3-10 min, finally slowly add MAX phase and continue stirring for 5-20 min; place the mixed solution in a heat-collecting magnetic stirrer, react at 50-70 °C for 24-48 h, and stir at a speed of 300-700 rpm; Among them, the mass volume ratio of LiF to hydrochloric acid is (1.5~5): (20~50) g / ml; the mass ratio of LiF to MAX phase is (1.5~5): (1~3); S402, after the reaction is completed and cooled to room temperature, the mixed solution is evenly distributed into several centrifuge tubes, centrifuged at 3000-4000 rpm for 5-10 min using a high-speed centrifuge, and then the supernatant is discarded, and deionized water is added to the centrifuge tubes, shaken well, and centrifuged repeatedly for 8-12 times; S403, after the centrifugation, the mixed solution is placed in a vortex oscillator, vortexed at a speed of 2000-2500 times per minute for 5-10 minutes, and the uniform mixed solution is placed in a centrifuge again, centrifuged at a speed of 1000-2000 rmp for 20-60 minutes, and the supernatant is collected, and the centrifugation process is repeated until the supernatant turns light green, and then the collection is stopped; S404. After removing impurities from the collected supernatant with filter cloth, collect the precipitate, pour the precipitate into a centrifuge tube, add deionized water and shake it in a vortex oscillator at a speed of 500 to 1500 times per minute for 5 to 10 minutes until it becomes a uniform MXene monolayer dispersion.
[0015] The volume ratio of the deionized water in S404 to the hydrochloric acid in S401 is (10-50): (20-50); S405, take the MXene monolayer dispersion, add deionized water, shake well, and then filter to obtain a monolayer MXene membrane colloid, wherein the concentration of the MXene membrane colloid is 20~50 mg·mL -1 ; S406, taking a monolayer MXene dispersion, mixing it with a conductive agent and MXene / MoS2 / TiO2 powder, and placing the mixture on a magnetic stirrer and stirring it at a rate of 300-600 rmp for 0.5-3 h to form a uniform slurry; S407. Use copper foil as the current collector and lay it flat on the coating machine. Wipe the surface of the copper foil clean with alcohol, then apply the slurry on the copper foil. Adjust the pusher scale to control the thickness of the electrode material coating to 10-20 μm. After coating, dry it in an oven at 50-80°C for 8-24 h. After drying, use a slicer to slice the area evenly coated with the slurry to obtain an electrode sheet.
[0016] Furthermore, the conductive agent in S406 includes any one of super P and acetylene black, and the mass ratio of the binder, the conductive agent and the active powder is (1~1.5): (1~2): (6.5~8).
[0017] Compared with the prior art, the beneficial effects of the present invention include the following points: (1) This paper proposes for the first time to construct a MXene / MoS2 / TiO2 ternary heterostructure and utilizes the synergistic effect of the three to obtain alkaline ions (Li + / Na + / K + ) Battery negative electrode materials. Among them, MoS2 has a high alkaline ion storage capacity due to its unique two-dimensional crystal structure, but its cycle stability is poor due to problems such as structural collapse. The good "accordion" structure of MXene can be used as a bearing point for MoS2, and with the help of MXene's high ionic and electronic conductivity, it provides a channel for the rapid transfer of charges in the composite electrode; although TiO2 has a low theoretical capacity, it has very excellent cycle stability and has a different voltage window from MoS2, so TiO2 has a certain inhibitory effect on the volume expansion of MoS2 loaded on the surface of MXene. The MXene / MoS2 / TiO2 ternary heterostructure designed based on this theoretical basis can provide a reference for the structural design of other similar electrode materials.
[0018] (2) The present invention proposes to use mixed acid as an etchant to etch the MAX phase to obtain MXene with a good layered structure. This method can effectively reduce the amount of HF acid used while ensuring the etching ability. Based on MAX etching, a simple freeze-drying and calcination preparation process is cleverly proposed to successfully obtain a high-purity MXene / MoS2 / TiO2 composite material. This method adsorbs the Mo source and S source containing NH4⁺ in the interlayer of MXene in the form of ions. NH4⁺ is equivalent to an intercalation ion that can prevent the stacking of MXene layers and play a role in expanding the layers. During the calcination process, NH4⁺ is converted into NH3 gas, and the Mo source and S source react in situ between the MXene layers to generate MoS2. At the same time, MXene contains a small amount of TiO2, and finally forms a MXene / MoS2 / TiO2 heterogeneous material. The MXene / MoS2 / TiO2 composite electrode exhibits good cycle stability as an alkaline ion battery negative electrode, and has significant scientific significance in the application of alkaline ion battery electrode materials.
[0019] (3) The present invention uses a single-layer MXene as a binder to prepare a negative electrode sheet for an alkaline ion battery, replacing the traditional binder (carboxymethyl cellulose, polyvinylidene fluoride). The single-layer MXene in the prepared electrode sheet can act as a binder due to its unique sheet structure and high ion / electronic conductivity, and can also completely wrap the MXene / MoS2 / TiO2 active powder, further improving the electrochemical performance of the MXene / MoS2 / TiO2 composite electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 is a scanning electron microscope photograph of MXene prepared by mixed acid etching in Example 4 of the present invention; Figure 2 is a scanning electron microscope photograph of the MXene / MoS2 / TiO2 composite material prepared in Example 4 of the present invention; Figure 3 is the X-ray diffraction spectrum of the MXene / MoS2 / TiO2 composite material prepared in Example 4 of the present invention; Figure 4 is a scanning electron microscope photograph of the single-layer MXene prepared in Example 4 of the present invention after filtration; Figure 5 is the X-ray diffraction spectrum of the single-layer MXene prepared in Example 4 of the present invention; Figure 6 It is a cycle performance diagram of the MXene / MoS2 / TiO2 composite material prepared in Example 4 and Comparative Examples 5-6 of the present invention; Figure 7 This is a scanning electron microscope photograph of MXene prepared in Comparative Example 1 of the present invention without mixed acid etching; Figure 8 is a scanning electron microscope photograph of the MXene / MoS2 / TiO2 composite material prepared in Comparative Example 2 of the present invention without freeze drying; Fig. 9 is the X-ray diffraction spectrum of the composite prepared in Comparative Example 3 of the present invention; Fig.10 It is the X-ray diffraction spectrum of the composite prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] This embodiment provides a method for preparing an alkaline ion battery negative electrode material, specifically a method for preparing a MXene / MoS2 / TiO2 composite electrode material for an ion battery negative electrode, comprising the following steps: S1. Use mixed acid method to etch MAX phase (Ti3AlC2) to obtain accordion-shaped MXene: In this embodiment, Ti3AlC2 is selected as the MAX phase material, but other types of MAX phase materials may also be selected according to specific application requirements.
[0024] S101. Select 45 wt.% HF, 36-38 wt.% HCl, and 98 wt.% H2SO4, measure 20 mL to 60 mL of a mixed solution of HF and HCl or H2SO4, and slowly add 0.5 to 3 g of MAX phase at a rate of 0.1 g / min to 0.6 g / min.
[0025] In this embodiment, the ratio, concentration, etching temperature and etching time of the mixed acid will have a significant impact on the etching effect. If the concentration of the acid solution is too high, the etching temperature is too high or the etching time is too long, it will lead to excessive etching, which will cause the destruction of the layered structure of the material. On the contrary, if the concentration of the acid solution is too low, the etching temperature is insufficient or the etching time is too short, the etching effect will be insufficient, and the metal atoms between the MXene layers cannot be effectively removed, so that the "accordion" structure with excellent layered characteristics cannot be formed.
[0026] In this embodiment, compared with the conventional multi-layer structure, the "accordion" structure has a uniform distribution of layered structures, without stacking, and each layer structure remains intact, which makes the etched MXene have a higher specific surface area and can provide abundant nucleation sites for MoS2; at the same time, the nucleation and growth process of MoS2 can also support the layered structure of MXene and prevent it from stacking again.
[0027] S102. After the addition is complete, the mixed solution is continuously stirred at 50°C to 70°C for 4 h to 24 h to obtain an etched MXene mixed solution.
[0028] S103. Use deionized water to centrifuge and wash the mixed solution. The speed of the centrifuge is maintained at 1000-4000 rpm. The centrifugation time is 5-20 min until the pH value of the supernatant is close to neutral. Dry and collect the centrifuged precipitate MXene.
[0029] S2. Powder containing MXene, Mo source and S source is obtained by freeze drying.
[0030] S201. Weigh 0.05-0.8 g of etched MXene and disperse it in 10-30 mL of deionized water. Then weigh 0.1-2.0 g of Mo source containing NH4⁺, such as ammonium tetrathiomolybdate, ammonium molybdate, and the corresponding S source, such as thioacetamide, thiourea, etc., and add them to the above solution. Ultrasonicate in a low-frequency ultrasonic disperser for 30-120 min to ensure that the MXene is evenly dispersed in the deionized water, and the raw materials containing Mo and S can be completely dissolved and adsorbed between the MXene layers by electrostatic action.
[0031] In this embodiment, there is no specific requirement for the specific frequency of the low-frequency ultrasonic disperser, and it only needs to ensure that it can achieve effective and uniform dispersion of MXene.
[0032] In this embodiment, a molybdenum source (Mo) and a sulfur source (S) are added in advance. During the freeze-drying process, Mo and S are adsorbed between MXene layers and on the surface in the form of ions through electrostatic forces. During the subsequent high-temperature calcination process, on the one hand, Mo and S react in situ to form MoS2 nanostructures, which also helps to prevent the restacking of MXene sheets; on the other hand, some end groups on the MXene surface undergo oxidation reactions at high temperatures to form TiO2. The presence of TiO2 not only increases the structural stability, but also effectively regulates the interaction with MoS2, thereby improving the overall performance of the composite material.
[0033] S202. Place the prepared uniform solution into a freeze dryer, freeze it at -30 ~ -70 °C for 3 ~ 12 h, and then evacuate and dry it at -30 ~ 0 °C for 4 ~ 12 h to obtain a dry powder.
[0034] S3. Calcine the powder containing MXene, Mo source and S source to prepare MXene / MoS2 / TiO2 composite material: S301. Take 0.1-1.0 g of dry powder and spread it evenly in a square porcelain boat. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. Keep the nitrogen gas flow rate at 50-200 sccm. Set the instrument to heat at 400-700°C for 0.5-5 h at a heating rate of 2-10°C / min.
[0035] The MXene surface formed after etching contains a variety of end groups (such as -F, -OH, etc.), which are easily oxidized under high temperature conditions and partially converted into TiO2. TiO2 exhibits structural stability during the charge and discharge process and has a different electrochemical potential window from MoS2. This property enables TiO2 to effectively inhibit the volume expansion of MoS2 during the charge and discharge process, thereby improving the cycle performance of the overall material.
[0036] S302. After the reaction is completed, samples are collected to obtain a MXene / MoS2 / TiO2 composite material.
[0037] This embodiment also provides an application of an alkaline ion battery negative electrode material, specifically an electrode sheet using MXene / MoS2 / TiO2 as active powder and a single layer of MXene as a binder; the preparation method thereof is as follows: S4. Use MXene / MoS2 / TiO2 as active powder and single-layer MXene as binder to prepare negative electrode sheets for alkaline ion batteries, and test the electrochemical properties.
[0038] S401, measure 10 ~ 20 mL of deionized water and pour it into a polytetrafluoroethylene bottle, add 20 ~ 50 mL of 11 ~ 13 mol·L -1 Stir the concentrated hydrochloric acid evenly to keep the concentration of HCl at 8~10.5 mol·L -1 , then slowly add 1.5~5 g of LiF and stir for 3~10 min, and finally slowly add 1~3 g of MAX phase (Ti3AlC2) and continue stirring for 5~20 min. Place the mixed solution in a heat-collecting magnetic stirrer and react at 50~70 ℃ for 24~48 h at a stirring speed of 300~700 rpm.
[0039] S402. After the reaction is completed and cooled to room temperature, the mixture is evenly distributed into several centrifuge tubes. Centrifuge at 3000-4000 rpm for 5-10 min in a high-speed centrifuge, then discard the supernatant. Add deionized water to the centrifuge tubes, shake well, and repeat this process for 8-12 times until the supernatant turns black.
[0040] S403. After centrifugation, place the mixed solution in a vortex oscillator and vortex at a speed of 2000-2500 times per minute for 5-10 min. Place the uniform mixed solution in a centrifuge again and centrifuge at a speed of 1000-2000 rmp for 20-60 min, then collect the supernatant. Repeat the centrifugation process until the supernatant turns light green and stop collecting.
[0041] S404. After removing impurities from the collected supernatant with a 300-600 mesh laboratory filter cloth, collect the precipitate, pour the precipitate into a centrifuge tube, add 10-50 mL of deionized water and shake well, vortex in a vortex oscillator at a speed of 500-1500 times per minute for 5-10 min until it becomes a uniform MXene monolayer dispersion.
[0042] S405, take 1 mL of the above dispersion, add 50-100 mL of deionized water, shake well, and filter to obtain a single-layer MXene After the film is completely dry, weigh it with a balance and calculate the concentration of MXene film colloid to be 20-50 mg·mL -1 .
[0043] S406. Use a rubber-tipped dropper to take 0.5~3 mL of single-layer MXene dispersion and add it to a 3~5 mL transparent small glass bottle. Then weigh 10~184 mg of conductive agent (super P, acetylene black) and 80~800 mg of pre-prepared MXene / MoS2 / TiO2 powder and add them to it, ensuring that the mass ratio of binder, conductive agent and active powder is (1~1.5):(1~2):(6.5~8). Place the mixture on a magnetic stirrer and stir at a rate of 300~600rmp for 0.5~3 h to form a uniform slurry.
[0044] S407, using copper foil as the current collector, lay it flat on the coating machine, wipe the surface of the copper foil with alcohol, apply the slurry on the copper foil, adjust the pusher scale to control the thickness of the electrode material coating to 10~20 μm, and dry it in an oven at 50~80℃ for 8~24 h after coating. After drying, use a slicer to slice the area evenly coated with the slurry to obtain a circular electrode sheet with a diameter of 10 mm.
[0045] S408. Use the prepared electrode sheet as the positive electrode and the lithium / sodium / potassium sheet as the negative electrode to assemble into a button half-cell in a glove box filled with argon atmosphere, and use the Blue Electric charge and discharge test system to test the cycle performance of the button cell.
[0046] Example 1 A MXene / MoS2 / TiO2 composite electrode for an alkaline ion battery negative electrode and a preparation method thereof, comprising the following steps: S1. Use mixed acid method to etch MAX phase (Ti3AlC2) to obtain accordion-shaped MXene: S101. Take 40 mL of commercially available 45 wt.% HF and 10 mL of 36-38 wt.% HCl to form a mixed solution, and slowly add 3 g of MAX phase at a rate of about 0.6 g / min.
[0047] S102. After the addition is complete, the mixed solution is continuously stirred at 70°C for 12 h to obtain an etched MXene mixed solution.
[0048] S103. The mixed solution is washed by centrifugation with deionized water. The speed of the centrifuge is maintained at 2000 r. The centrifugation time is 5 min until the pH value of the supernatant is close to neutral. The centrifuged precipitate MXene is collected by drying.
[0049] S2. Powder containing MXene, Mo source and S source is obtained by freeze drying.
[0050] S201. Weigh 0.05 g of the etched MXene and disperse it in 10 mL of deionized water. Then weigh 0.1 g of ammonium tetrathiomolybdate and add it to the above solution. Ultrasonicate it in a low-frequency ultrasonic disperser for 30 min to ensure that the MXene is evenly dispersed in the deionized water and the raw materials containing Mo and S can be completely dissolved and adsorbed between the MXene layers by electrostatic action.
[0051] S202. Place the prepared uniform solution into a freeze dryer, freeze it at -30°C for 5 h, and then evacuate and dry it at -30°C for 4 h to obtain a dry powder.
[0052] S3. Calcine the powder containing MXene, Mo source and S source to prepare MXene / MoS2 / TiO2 composite material: S301. Take 0.1 g of dry powder and spread it evenly in a square porcelain boat. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. The nitrogen gas flow rate is maintained at 50 sccm. Set the instrument to keep the temperature at 400 ℃ for 3 h at a heating rate of 2 ℃ / min.
[0053] S302. After the reaction is completed, samples are collected to obtain a MXene / MoS2 / TiO2 composite material.
[0054] S4. Prepare electrode sheets with MXene / MoS2 / TiO2 as active powder and single-layer MXene as binder, and test the electrochemical performance.
[0055] S401, measure 10 mL of deionized water and pour it into a polytetrafluoroethylene bottle, add 20 mL of 11 mol·L -1 Stir the concentrated hydrochloric acid evenly to keep the concentration of HCl at 8 mol·L -1 Then, 1.5 g of LiF was slowly added and stirred for 3 min, and finally 1 g of MAX phase was slowly added and stirred for 5 min. The mixed solution was placed in a heat-collecting magnetic stirrer and reacted at 50 °C for 36 h with a stirring speed of 300 rpm.
[0056] S402. After the reaction is completed and cooled to room temperature, the mixture is evenly distributed into several centrifuge tubes. Centrifuge at 3000 rpm for 5 min in a high-speed centrifuge and then the supernatant is discarded. Deionized water is added to the centrifuge tubes and shaken well. Repeat this process for 8 times until the supernatant turns black.
[0057] S403. After centrifugation, the mixed solution is placed in a vortex oscillator and vortexed at a speed of 2000 times per minute for 10 minutes. The uniform mixed solution is placed in a centrifuge again and centrifuged at a speed of 1000 rpm for 60 minutes, and the supernatant is collected. The centrifugation process is repeated until the supernatant turns light green and the collection is stopped.
[0058] S404. The collected supernatant was filtered through a 300-mesh laboratory filter cloth to remove impurities and then the precipitate was collected. The precipitate was poured into a centrifuge tube and then added into 10 mL of deionized water and shaken well. The mixture was vortexed in a vortex oscillator at a speed of 500 times per minute for 10 minutes until it became a uniform MXene monolayer dispersion.
[0059] S405. Take 1 mL of the above dispersion, add 50 mL of deionized water, shake well, and filter to obtain a single-layer MXene film. After the film is completely dry, weigh it with a balance and calculate the concentration of MXene colloid to be 20 mg·mL -1 .
[0060] S406. Use a rubber-tipped dropper to take 0.5 mL of single-layer MXene dispersion and add it to a 3 mL transparent small glass bottle. Then weigh 10 mg of conductive agent super P and 80 mg of pre-prepared MXene / MoS2 / TiO2 powder and add them to it, ensuring that the mass ratio of binder, conductive agent and active powder is 1:1:8. Place the mixture on a magnetic stirrer and stir at a rate of 300 rpm for 0.5 h to form a uniform slurry.
[0061] S407, using copper foil as the current collector, lay it flat on the coating machine, wipe the surface of the copper foil with alcohol, apply the slurry on the copper foil, adjust the pusher scale to control the thickness of the electrode material coating to 10 μm, and dry it in an oven at 50 °C for 24 h after coating. After drying, use a slicer to slice the area where the slurry is evenly coated to obtain a circular electrode sheet with a diameter of 10 mm.
[0062] S408. The prepared electrode sheet was used as the positive electrode, the lithium sheet as the negative electrode, the microporous polypropylene film (Celgard 2400) as the separator, and the electrolyte was 1 mol / L LiPF6 dissolved in a mixed solution of ethyl carbonate (EC), methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1. A button half-cell was assembled in a glove box filled with argon atmosphere, and the cycle performance of the button cell was tested using the Blue Electric charge and discharge test system.
[0063] Example 2 A MXene / MoS2 / TiO2 composite electrode for an alkaline ion battery negative electrode and a preparation method thereof, comprising the following steps: S1. Use mixed acid method to etch MAX phase (Ti3AlC2) to obtain accordion-shaped MXene: S101. Take 20 mL of commercially available 45 wt.% HF and 40 mL of 36-38 wt.% HCl to form a mixed solution, and slowly add 2 g of MAX phase at a rate of about 0.5 g / min.
[0064] S102. After the addition is complete, the mixed solution is continuously stirred at 60°C for 8 h to obtain an etched MXene mixed solution.
[0065] S103. The mixed solution is centrifuged and washed with deionized water. The speed of the centrifuge is maintained at 1000 r. The centrifugation time is 10 min until the pH value of the supernatant is close to neutral. The centrifuged precipitate MXene is collected by drying.
[0066] S2. Powder containing MXene, Mo source and S source is obtained by freeze drying.
[0067] S201. Weigh 0.15 g of the etched MXene and disperse it in 20 mL of deionized water. Then weigh 0.45 g of ammonium molybdate and 0.35 g of thiourea and add them to the above solution. Ultrasonicate in a low-frequency ultrasonic disperser for 60 min to ensure that the MXene is evenly dispersed in the deionized water and that the raw materials containing Mo and S can be completely dissolved and adsorbed between the MXene layers by electrostatic action.
[0068] S202. Place the prepared uniform solution into a freeze dryer, freeze it at -50°C for 8 h, and then evacuate and dry it at -20°C for 8 h to obtain a dry powder.
[0069] S3. Calcine the powder containing MXene, Mo source and S source to prepare MXene / MoS2 / TiO2 composite material: S301. Take 0.3 g of dry powder and spread it flat in a square porcelain boat. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. The nitrogen gas flow rate is maintained at 100 sccm. Set the instrument to keep the temperature at 500 °C for 5 h at a heating rate of 5 °C / min.
[0070] S302. After the reaction is completed, samples are collected to obtain a MXene / MoS2 / TiO2 composite material.
[0071] S4. Prepare electrode sheets with MXene / MoS2 / TiO2 as active powder and single-layer MXene as binder, and test the electrochemical performance.
[0072] S401, measure 10 mL of deionized water and pour it into a polytetrafluoroethylene bottle, add 30 mL of 13 mol·L -1 Stir the concentrated hydrochloric acid evenly to keep the concentration of HCl at 9 mol·L -1 , then slowly add 2 g of LiF and stir for 5 min, and finally slowly add 1.5 g of MAX phase and continue stirring for 10 min. The mixed solution was placed in a heat-collecting magnetic stirrer and reacted at 60 °C for 24 h with a stirring speed of 400 rpm.
[0073] S402. After the reaction is completed and cooled to room temperature, the mixture is evenly distributed into several centrifuge tubes. Centrifuge at 3500 rpm for 8 min using a high-speed centrifuge and then discard the supernatant. Add deionized water to the centrifuge tubes and shake well. Repeat this process and centrifuge for 9 times until the supernatant turns black.
[0074] S403. After centrifugation, the mixed solution is placed in a vortex oscillator and vortexed at a speed of 2200 times per minute for 8 minutes. The uniform mixed solution is placed in a centrifuge again and centrifuged at a speed of 1800 rpm for 40 minutes, and the supernatant is collected. The centrifugation process is repeated until the supernatant turns light green and the collection is stopped.
[0075] S404. The collected supernatant was filtered through a 400-mesh laboratory filter cloth to remove impurities and then the precipitate was collected. The precipitate was poured into a centrifuge tube and then added into 20 mL of deionized water and shaken well. The mixture was vortexed in a vortex oscillator at a speed of 600 times per minute for 8 min until it became a uniform MXene monolayer dispersion.
[0076] S405. Take 1 mL of the above dispersion, add 60 mL of deionized water, shake well, and filter to obtain a single-layer MXene film. After the film is completely dry, weigh it with a balance and calculate the concentration of MXene colloid to be 28 mg·mL -1 .
[0077] S406. Use a rubber-tipped dropper to take 1 mL of single-layer MXene dispersion and add it to a 3 mL transparent small glass bottle. Then weigh 56 mg of conductive agent acetylene black and 196 mg of pre-prepared MXene / MoS2 / TiO2 powder and add them to it, ensuring that the mass ratio of binder, conductive agent and active powder is 1:2:7. Place the mixture on a magnetic stirrer and stir at a rate of 400 rpm for 1 h to form a uniform slurry.
[0078] S407, using copper foil as the current collector, lay it flat on the coating machine, wipe the surface of the copper foil with alcohol, apply the slurry on the copper foil, adjust the pusher scale to control the thickness of the electrode material coating to 20 μm, and dry it in an oven at 60 °C for 18 h after coating. After drying, use a slicer to slice the area where the slurry is evenly coated to obtain a circular electrode sheet with a diameter of 10 mm.
[0079] S408. The prepared electrode sheet was used as the positive electrode, the sodium sheet as the negative electrode, the glass fiber membrane as the separator, and the electrolyte was 1 mol / L NaClO4 dissolved in a mixed solution of ethylene carbonate (EC) and propylene carbonate (PC) with a volume ratio of 1:1 and 5 vol% fluoroethylene carbonate (FEC). A button half-cell was assembled in a glove box filled with argon atmosphere, and the cycle performance of the button cell was tested using the Blue Electric charge and discharge test system.
[0080] Example 3 A MXene / MoS2 / TiO2 composite electrode for an alkaline ion battery negative electrode and a preparation method thereof, comprising the following steps: S1. Use mixed acid method to etch MAX phase (Ti3AlC2) to obtain accordion-shaped MXene: S101. Take 10 mL of commercially available 45 wt.% HF and 10 mL of 98 wt.% H2SO4 to form a mixed solution, and slowly add 0.5 g of MAX phase at a rate of about 0.1 g / min.
[0081] S102. After the addition is complete, the mixed solution is continuously stirred at 50°C for 24 h to obtain an etched MXene mixed solution.
[0082] S103. The mixed solution is centrifuged and washed with deionized water. The speed of the centrifuge is maintained at 3500r. The centrifugation time is 20 min until the pH value of the supernatant is close to neutral. The centrifuged precipitate MXene is collected by drying.
[0083] S2. Powder containing MXene, Mo source and S source is obtained by freeze drying.
[0084] S201. Weigh 0.3 g of the etched MXene and disperse it in 20 mL of deionized water. Then weigh 0.9 g of ammonium molybdate and 0.69 g of thioacetamide and add them to the above solution. Ultrasonicate in a low-frequency ultrasonic disperser for 90 min to ensure that the MXene is evenly dispersed in the deionized water and that the raw materials containing Mo and S can be completely dissolved and adsorbed between the MXene layers by electrostatic action.
[0085] S202. Place the prepared uniform solution into a freeze dryer, freeze it at -70°C for 3 h, and then evacuate and dry it at -10°C for 8 h to obtain a dry powder.
[0086] S3. Calcine the powder containing MXene, Mo source and S source to prepare MXene / MoS2 / TiO2 composite material: S301. Take 0.5 g of dry powder and spread it flat in a square porcelain boat. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. The nitrogen gas flow rate is maintained at 200 sccm. Set the instrument to keep the temperature at 600 °C for 3 h at a heating rate of 10 °C / min.
[0087] S302. After the reaction is completed, samples are collected to obtain a MXene / MoS2 / TiO2 composite material.
[0088] S4. Prepare electrode sheets with MXene / MoS2 / TiO2 as active powder and single-layer MXene as binder, and test the electrochemical performance.
[0089] S401, measure 15 mL of deionized water and pour it into a polytetrafluoroethylene bottle, add 25 mL of 12 mol·L -1 Stir the concentrated hydrochloric acid evenly to keep the concentration of HCl at 10.5 mol·L -1 , then slowly add 5 g of LiF and stir for 10 min, and finally slowly add 3 g of MAX phase and continue stirring for 20 min. The mixed solution was placed in a heat collecting magnetic stirrer and reacted at 70 °C for 24 h with a stirring speed of 700 rpm.
[0090] S402. After the reaction is completed and cooled to room temperature, the mixture is evenly distributed into several centrifuge tubes. Centrifuge at 4000 rpm for 10 min in a high-speed centrifuge and then the supernatant is discarded. Deionized water is added to the centrifuge tubes and shaken well. Repeat this process for 12 times until the supernatant turns black.
[0091] S403. After centrifugation, the mixed solution is placed in a vortex oscillator and vortexed at a speed of 2500 times per minute for 5 minutes. The uniform mixed solution is placed in a centrifuge again and centrifuged at a speed of 2000 rpm for 50 minutes, and the supernatant is collected. The centrifugation process is repeated until the supernatant turns light green and the collection is stopped.
[0092] S404. The collected supernatant was filtered through a 600-mesh laboratory filter cloth to remove impurities and then the precipitate was collected. The precipitate was poured into a centrifuge tube and then added into 50 mL of deionized water and shaken well. The mixture was vortexed in a vortex oscillator at a speed of 1500 times per minute for 5 minutes until it became a uniform MXene monolayer dispersion.
[0093] S405. Take 1 mL of the above dispersion, add 100 mL of deionized water, shake well, and filter to obtain a single-layer MXene film. After the film is completely dry, weigh it with a balance and calculate the concentration of MXene colloid to be 50 mg·mL -1 .
[0094] S406. Use a rubber-tipped dropper to take 2 mL of single-layer MXene dispersion and add it to a 5 mL transparent small glass bottle. Then weigh 100 mg of conductive agent acetylene black and 800 mg of pre-prepared MXene / MoS2 / TiO2 powder and add them to it, ensuring that the mass ratio of binder, conductive agent and active powder is 1:1:8. Place the mixture on a magnetic stirrer and stir at a rate of 600 rpm for 3 h to form a uniform slurry.
[0095] S407, using copper foil as the current collector, lay it flat on the coating machine, wipe the surface of the copper foil with alcohol, apply the slurry on the copper foil, adjust the pusher scale to control the thickness of the electrode material coating to 15 μm, and dry it in an oven at 70 °C for 12 h after coating. After drying, use a slicer to slice the area where the slurry is evenly coated to obtain a circular electrode sheet with a diameter of 10 mm.
[0096] S408, using the prepared electrode sheet as the positive electrode, the potassium sheet as the negative electrode, the glass fiber membrane as the separator, and the electrolyte being 1.0 mol / L KFSI dissolved in a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. Assemble into a button half-cell in a glove box filled with argon atmosphere, and use the Blue Electric charge and discharge test system to test the cycle performance of the button cell.
[0097] Example 4 A MXene / MoS2 / TiO2 composite electrode for an alkaline ion battery negative electrode and a preparation method thereof, comprising the following steps: S1. Use mixed acid method to etch MAX phase (Ti3AlC2) to obtain accordion-shaped MXene: S101. Take 5 mL of commercially available 45 wt.% HF and 25 mL of 98 wt.% H2SO4 to form a mixed solution, and slowly add 1 g of MAX phase at a rate of about 0.2 g / min.
[0098] S102. After the addition is complete, the mixed solution is continuously stirred at 60°C for 4 h to obtain an etched MXene mixed solution.
[0099] S103. The mixed solution is centrifuged and washed with deionized water. The speed of the centrifuge is maintained at 3000r. The centrifugation time is 8 min until the pH value of the supernatant is close to neutral. The centrifuged precipitate MXene is collected by drying.
[0100] S2. Powder containing MXene, Mo source and S source is obtained by freeze drying.
[0101] S201. Weigh 0.5 g of the etched MXene and disperse it in 30 mL of deionized water. Then weigh 2 g of ammonium tetrathiomolybdate and add it to the above solution. Ultrasonicate it in a low-frequency ultrasonic disperser for 90 min to ensure that the MXene is evenly dispersed in the deionized water and the raw materials containing Mo and S can be completely dissolved and adsorbed between the MXene layers by electrostatic action.
[0102] S202. Place the prepared uniform solution into a freeze dryer, freeze it at -50 °C for 10 h, and then vacuum dry it at -10 °C for 10 h to obtain a dry powder.
[0103] S3. Calcine the powder containing MXene, Mo source and S source to prepare MXene / MoS2 / TiO2 composite material: S301. Take 0.8 g of dry powder and spread it evenly in a square porcelain boat. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. The nitrogen gas flow rate is maintained at 100 sccm. Set the instrument to keep the temperature at 600 °C for 2 h at a heating rate of 5 °C / min.
[0104] S302. After the reaction is completed, samples are collected to obtain a MXene / MoS2 / TiO2 composite material.
[0105] The morphology of MXene after mixed acid etching was observed using a field emission scanning electron microscope (SEM) model S4800. Figure 1 As shown in Figure 2, MXene exhibits an obvious "accordion" structure; the SEM of the final MXene / MoS2 / TiO2 composite material is shown in Figure 2. Figure 2As shown, MoS2 and TiO2 nanocrystals are uniformly distributed between the layers and on the surface of MXene; the MXene / MoS2 / TiO2 composite powder prepared in this embodiment was analyzed using a German Bruker D8 Advance model X-ray diffractometer, as shown Figure 3 As shown, the physical phase of the composite mainly corresponds to the 3R phase MoS2 with JCPDS number 17-0744 and TiO2 with JCPDS number 21-1272. At the same time, there are MXene peaks at 27.2° and 60.5°, which indicates that the prepared MXene / MoS2 / TiO2 composite has high purity and no other impurity phases.
[0106] S4. Prepare electrode sheets with MXene / MoS2 / TiO2 as active powder and single-layer MXene as binder, and test the electrochemical performance.
[0107] S401, measure 12.5 mL of deionized water and pour it into a polytetrafluoroethylene bottle, add 37.5 mL of 12 mol·L -1 Stir the concentrated hydrochloric acid evenly to keep the concentration of HCl at 9 mol·L -1 , then slowly add 3 g of LiF and stir for 5 min, and finally slowly add 1.5 g of MAX phase and continue stirring for 10 min. The mixed solution was placed in a heat collecting magnetic stirrer and reacted at 60 °C for 30 h with a stirring speed of 500 rpm.
[0108] S402. After the reaction is completed and cooled to room temperature, the mixture is evenly distributed into several centrifuge tubes. Centrifuge at 3000 rpm for 5 min in a high-speed centrifuge and then the supernatant is discarded. Deionized water is added to the centrifuge tubes and shaken well. Repeat this process for 9 times until the supernatant turns black.
[0109] S403. After centrifugation, the mixed solution is placed in a vortex oscillator and vortexed at a speed of 2400 times per minute for 7 minutes. The uniform mixed solution is placed in a centrifuge again and centrifuged at a speed of 1500 rpm for 30 minutes, and the supernatant is collected. The centrifugation process is repeated until the supernatant turns light green and the collection is stopped.
[0110] S404. The collected supernatant was filtered through a 400-mesh laboratory filter cloth to remove impurities and then the precipitate was collected. The precipitate was poured into a centrifuge tube and then added into 30 mL of deionized water and shaken well. The mixture was vortexed in a vortex oscillator at a speed of 1000 times per minute for 6 minutes until it became a uniform MXene monolayer dispersion.
[0111] S405. Take 1 mL of the above dispersion, add 80 mL of deionized water, shake well, and filter to obtain a single-layer MXene film. After the film is completely dry, weigh it with a balance and calculate the concentration of MXene colloid to be 40 mg·mL -1 .
[0112] The single-layer MXene after filtration was observed using a field emission scanning electron microscope (SEM) of model S4800. Figure 4 As shown, MXene exhibits a distinct lamella structure; the single-layer MXene prepared in this embodiment was analyzed using a German Bruker D8 Advance model X-ray diffractometer, as shown Figure 5 As shown, there is an obvious diffraction peak of MXene at 6.2°, corresponding to the (002) crystal plane of Ti3C2 that appears after etching.
[0113] S406. Use a rubber-tipped dropper to take 2 mL of single-layer MXene dispersion and add it to a 5 mL transparent small glass bottle. Then weigh 160 mg of conductive agent super P and 560 mg of pre-prepared MXene / MoS2 / TiO2 powder and add them. Ensure that the mass ratio of binder, conductive agent and active powder is 1:2:7. Place the mixture on a magnetic stirrer and stir at 500 rpm for 1 h to form a uniform slurry.
[0114] S407, using copper foil as the current collector, lay it flat on the coating machine, wipe the surface of the copper foil with alcohol, and then apply three kinds of slurries on different positions of the copper foil respectively, adjust the pusher scale to control the thickness of the electrode material coating to 15 μm, and dry it in an oven after coating at 80 ℃ for 8 h. After drying, use a slicer to slice the parts evenly coated with the slurry to obtain three kinds of circular electrode sheets with a diameter of 10 mm.
[0115] S408, using the prepared electrode sheet as the positive electrode, the potassium sheet as the negative electrode, the glass fiber membrane as the separator, and the electrolyte being 1.0 mol / L KFSI dissolved in a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. Assemble into a button half-cell in a glove box filled with argon atmosphere, and use the Blue Electric charge and discharge test system to test the cycle performance of the button cell. Figure 6 For a button half-cell at 1000 mA·g -1 Cycling performance diagram. After 100 cycles, the electrode capacity with single-layer MXene as binder remains at 149.6 mAh g -1 .
[0116] Example 5 A MXene / MoS2 / TiO2 composite electrode for an alkaline ion battery negative electrode and a preparation method thereof, comprising the following steps: S1. Use mixed acid method to etch MAX phase (Ti3AlC2) to obtain accordion-shaped MXene: S101. Take 25 mL of commercially available 45 wt.% HF and 15 mL of 36-38 wt.% H2SO4 to form a mixed solution, and slowly add 1.5 g of MAX phase at a rate of about 0.4 g / min.
[0117] S102. After the addition is complete, the mixed solution is continuously stirred at 50°C for 16 h to obtain an etched MXene mixed solution.
[0118] S103. The mixed solution is centrifuged and washed with deionized water. The speed of the centrifuge is maintained at 4000 rpm. The centrifugation time is 12 min until the pH value of the supernatant is close to neutral. The centrifuged precipitate MXene is collected by drying.
[0119] S2. Powder containing MXene, Mo source and S source is obtained by freeze drying.
[0120] S201. Weigh 0.8 g of the etched MXene and disperse it in 30 mL of deionized water. Then weigh 1.5 g of ammonium tetrathiomolybdate and add it to the above solution. Ultrasonicate it in a low-frequency ultrasonic disperser for 120 min to ensure that the MXene is evenly dispersed in the deionized water and the raw materials containing Mo and S can be completely dissolved and adsorbed between the MXene layers by electrostatic action.
[0121] S202. Place the prepared uniform solution into a freeze dryer, freeze it at -60°C for 12 h, and then vacuum dry it at 0°C for 12 h to obtain a dry powder.
[0122] S3. Calcine the powder containing MXene, Mo source and S source to prepare MXene / MoS2 / TiO2 composite material: S301. Take 1.0 g of dry powder and spread it flat in a square porcelain boat. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. The nitrogen gas flow rate is maintained at 50 sccm. Set the instrument to keep the temperature at 700 °C for 1 h at a heating rate of 10 °C / min.
[0123] S302. After the reaction is completed, samples are collected to obtain a MXene / MoS2 / TiO2 composite material.
[0124] S4. Prepare electrode sheets with MXene / MoS2 / TiO2 as active powder and single-layer MXene as binder, and test the electrochemical performance.
[0125] S401, measure 20 mL of deionized water and pour it into a polytetrafluoroethylene bottle, add 50 mL of 12 mol·L -1 Stir the concentrated hydrochloric acid evenly to keep the concentration of HCl at 8.5 mol·L -1 , then slowly add 4 g of LiF and stir for 8 min, and finally slowly add 2.5 g of MAX phase and continue stirring for 15 min. The mixed solution was placed in a heat collecting magnetic stirrer and reacted at 50 °C for 48 h with a stirring speed of 600 rpm.
[0126] S402. After the reaction is completed and cooled to room temperature, the mixture is evenly distributed into several centrifuge tubes. Centrifuge at 4000 rpm for 5 min in a high-speed centrifuge and then the supernatant is discarded. Deionized water is added to the centrifuge tubes and shaken well. Repeat this process for 10 times until the supernatant turns black.
[0127] S403. After centrifugation, the mixed solution was placed in a vortex oscillator and vortexed at a speed of 2000 times per minute for 8 minutes. The uniform mixed solution was placed in a centrifuge again and centrifuged at a speed of 1500 rpm for 20 minutes, and the supernatant was collected. The centrifugation process was repeated until the supernatant turned light green and then the collection was stopped.
[0128] S404. The collected supernatant was filtered through a 500-mesh laboratory filter cloth to remove impurities and then the precipitate was collected. The precipitate was poured into a centrifuge tube and then added into 40 mL of deionized water and shaken well. The mixture was vortexed in a vortex oscillator at a speed of 800 times per minute for 5 min until it became a uniform MXene monolayer dispersion.
[0129] S405. Take 1 mL of the above dispersion, add 80 mL of deionized water, shake well, and filter to obtain a single-layer MXene film. After the film is completely dry, weigh it with a balance and calculate the concentration of MXene colloid to be 46 mg·mL -1 .
[0130] S406. Use a rubber-tipped dropper to take 3 mL of single-layer MXene dispersion and add it to a 5 mL transparent small glass bottle. Then weigh 184 mg of conductive agent super P and 598 mg of pre-prepared MXene / MoS2 / TiO2 powder and add them to it, ensuring that the mass ratio of binder, conductive agent and active powder is 1.5:2:6.5. Place the mixture on a magnetic stirrer and stir at a rate of 600 rpm for 2 hours to form a uniform slurry.
[0131] S407, using copper foil as the current collector, lay it flat on the coating machine, wipe the surface of the copper foil with alcohol, apply the slurry on the copper foil, adjust the pusher scale to control the thickness of the electrode material coating to 15 μm, and dry it in an oven at 60 °C for 12 h after coating. After drying, use a slicer to slice the area where the slurry is evenly coated to obtain a circular electrode sheet with a diameter of 10 mm.
[0132] S408. The prepared electrode sheet was used as the positive electrode, the sodium sheet as the negative electrode, the glass fiber membrane as the separator, and the electrolyte was 1 mol / L NaClO4 dissolved in a mixed solution of ethylene carbonate (EC) and propylene carbonate (PC) with a volume ratio of 1:1 and 5 vol% fluoroethylene carbonate (FEC). A button half-cell was assembled in a glove box filled with argon atmosphere, and the cycle performance of the button cell was tested using the Blue Electric charge and discharge test system.
[0133] Comparative Example 1 In S1, 5 mL of a mixed solution of commercially available HF with a mass fraction of 45 wt.% and 25 mL of H2SO4 with a mass fraction of 98 wt.% was replaced with 30 mL of deionized water, and the remaining steps were the same as those in Example 4.
[0134] like Figure 7 , the scanning electron microscope (SEM) image of the MXene material obtained in Comparative Example 1 failed to show an "accordion" structure with good stratification, but instead showed a simple stacking of the layered structure, resulting in a decrease in the battery cycle stability.
[0135] Comparative Example 2 In S2, a powder containing MXene, Mo source and S source is prepared by simple raw material mixing, thereby replacing the freeze-drying process, and the remaining steps are the same as those in Example 4. Figure 8 The nanoparticles in the SEM of Comparative Example 2 have obvious agglomeration phenomenon. This comparison result shows that the freeze-drying process can make the Mo source and S source uniformly adsorbed on the surface and interlayer of MXene in the form of ions, and the calcination process can make MoS2 uniformly nucleated in situ; while the samples that directly mix MXene with Mo source and S source often cause particle agglomeration due to uneven mixing.
[0136] Comparative Example 3 S3, take 0.8 g of dry powder and spread it in a square porcelain boat, then place the porcelain boat in a vacuum tube furnace filled with nitrogen, keep the nitrogen gas flow rate at 100 sccm, set the instrument to keep the temperature at 300 ° C for 2 h at a heating rate of 5 ° C / min. The remaining steps are the same as in Example 4. Fig. 9 As shown, under this process condition, the Mo source and the S source cannot react to generate MoS2 and still exist in the form of raw materials.
[0137] Comparative Example 4 S3, take 0.8 g of dry powder and spread it in a square porcelain boat, then place the porcelain boat in a vacuum tube furnace filled with nitrogen, keep the nitrogen gas flow rate at 100 sccm, set the instrument to keep the temperature at 800 ° C for 2 h at a heating rate of 5 ° C / min. The remaining steps are the same as in Example 4. Fig.10 As shown, under this process condition, most of MoS2 is transformed into MoO2, showing a physical phase in which MoS2 and MoO2 coexist.
[0138] Comparative Example 5 S406, weigh 80 mg CMC; then weigh 160 mg conductive agent super P and 560 mg and mix them evenly in a mortar, add appropriate amount of deionized water and grind to form a slurry, ensuring that the mass ratio of binder, conductive agent and active powder is 1:2:7, place the mixture on a magnetic stirrer and stir at a rate of 500 rpm for 1 h to form a uniform slurry.
[0139] The remaining steps are the same as those in Example 4.
[0140] Comparative Example 6 S406, weigh 80 mg PVDF, then weigh 160 mg conductive agent super P and 560 mg, mix them evenly in a mortar, add appropriate amount of deionized water and grind to form a slurry, ensuring that the mass ratio of binder, conductive agent and active powder is 1:2:7, place the mixture on a magnetic stirrer and stir at a rate of 500 rpm for 1 h to form a uniform slurry.
[0141] The remaining steps are the same as those in Example 4.
[0142] The button half-cells assembled from the materials prepared in Example 4 and Comparative Examples 5-6 were -1 The cycle performance of Figure 6 After 100 cycles, the electrode capacity using the single-layer MXene in Example 4 as the binder remained at 149.6 mAh·g -1 The electrode capacity of Comparative Example 5 with CMC as binder was maintained at 47.8 mAh g -1 The electrode capacity of the PVDF-based electrode in Comparative Example 6 was maintained at 6.6 mAh g -1 .
[0143] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0144] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing an alkaline ion battery negative electrode material, characterized in that: The following steps are involved: S1. Etching the MAX phase material using a mixed acid to obtain etched MXene; S2. Obtaining a powder containing MXene, Mo source and S source simultaneously by freeze drying; S3. Calcine the powder containing MXene, Mo source and S source to obtain a MXene / MoS2 / TiO2 composite material.
2. The method for preparing a negative electrode material for an alkaline ion battery according to claim 1, characterized in that: The mixed acid obtained in S1 is a mixture of either HCl or H2SO4 and HF; wherein the volume ratio of HF to either HCl or H2SO4 is (5~40):(10~40).
3. The method for preparing a negative electrode material for an alkaline ion battery according to claim 1, characterized in that: During the etching process of S1, the mass volume ratio of the MAX phase material to the mixed acid is (0.5-3): (20-60) g / ml; The etching process is as follows: the mixed acid is added to the MAX phase at a rate of 0.1 g / min~0.6 g / min. After complete addition, the mixed solution is continuously stirred at 50℃~70℃ for 4 h~24 h to obtain the etched MXene mixed solution; the mixed solution is centrifuged and washed with deionized water, the centrifuge speed is maintained at 1000~4000rpm, the centrifugation time is 5~20min, until the pH value of the supernatant is neutral, and the centrifuged precipitate MXene is collected by drying.
4. The method for preparing a negative electrode material for an alkaline ion battery according to claim 1, characterized in that: The specific process of S2 is: S201, disperse the etched MXene in deionized water; add Mo source and S source containing NH4⁺, and ultrasonicate in an ultrasonic disperser for 30-120 min; S202. Freeze-dry the solution after ultrasonic dispersion at -30 ~ -70 °C for 3 ~ 12 h, and then vacuum dry it at -30 ~ 0 °C for 4 ~ 12 h to obtain a dry powder containing MXene, Mo source and S source.
5. The method for preparing a negative electrode material for an alkaline ion battery according to claim 4, characterized in that: The mass volume ratio of the etched MXene to deionized water described in S201 is (0.05~0.8): (10~30) g / ml.
6. The method for preparing a negative electrode material for an alkaline ion battery according to claim 4, characterized in that: The Mo source in S201 is specifically any one of ammonium tetrathiomolybdate and ammonium molybdate, and the S source is specifically any one of thioacetamide and thiourea; the mass ratio of the MXene to the sum of the Mo source and S is (0.05~0.8):(0.1~2.0); when the Mo source is ammonium tetrathiomolybdate, the S source is not introduced.
7. The method for preparing a negative electrode material for an alkaline ion battery according to claim 1, characterized in that: The specific process of S3 is as follows: the powder containing MXene, Mo source and S source is dried and kept at 400-700°C for 0.5-5 h at a heating rate of 2-10°C / min in a nitrogen atmosphere with a flow rate of 50-200 sccm; after the reaction, a MXene / MoS2 / TiO2 composite material is obtained.
8. A MXene / MoS2 / TiO2 composite material prepared by the method for preparing an alkaline ion battery negative electrode material as described in any one of claims 1 to 7.
9. The use of an alkaline ion battery negative electrode material as claimed in claim 8, characterized in that: An electrode sheet using a MXene / MoS2 / TiO2 composite material as active powder and a single layer of MXene as a binder; the preparation method of the electrode sheet is as follows: S401. Pour deionized water into a polytetrafluoroethylene bottle, then add concentrated hydrochloric acid and stir to keep the concentration of HCl at 8~10.5 mol·L -1 , then slowly add LiF and stir for 3-10 min, finally slowly add MAX phase and continue stirring for 5-20 min; place the mixed solution in a heat-collecting magnetic stirrer, react at 50-70 °C for 24-48 h, and stir at a speed of 300-700 rpm; Among them, the mass volume ratio of LiF to hydrochloric acid is (1.5~5): (20~50) g / ml; the mass ratio of LiF to MAX phase is (1.5~5): (1~3); S402, after the reaction is completed and cooled to room temperature, the mixed solution is evenly distributed into several centrifuge tubes, centrifuged at 3000-4000 rpm for 5-10 min using a high-speed centrifuge, and then the supernatant is discarded, and deionized water is added to the centrifuge tubes, shaken well, and centrifuged repeatedly for 8-12 times; S403, after the centrifugation, the mixed solution is placed in a vortex oscillator, vortexed at a speed of 2000-2500 times per minute for 5-10 minutes, and the uniform mixed solution is placed in a centrifuge again, centrifuged at a speed of 1000-2000 rmp for 20-60 minutes, and the supernatant is collected, and the centrifugation process is repeated until the supernatant turns light green, and then the collection is stopped; S404, the collected supernatant is filtered to remove impurities and then the precipitate is collected, the precipitate is poured into a centrifuge tube, and then deionized water is added and shaken in a vortex oscillator at a speed of 500 to 1500 times per minute for 5 to 10 minutes until it becomes a uniform MXene monolayer dispersion; The volume ratio of the deionized water in S404 to the hydrochloric acid in S401 is (10-50): (20-50); S405, take the MXene monolayer dispersion, add deionized water, shake well, and then filter to obtain a monolayer MXene membrane colloid, wherein the concentration of the MXene membrane colloid is 20~50 mg·mL -1 ; S406, taking a monolayer MXene dispersion, mixing it with a conductive agent and MXene / MoS2 / TiO2 powder, and placing the mixture on a magnetic stirrer and stirring it at a rate of 300-600 rmp for 0.5-3 h to form a uniform slurry; S407. Use copper foil as the current collector and lay it flat on the coating machine. Wipe the surface of the copper foil with alcohol, then apply the slurry on the copper foil. Adjust the pusher scale to control the thickness of the electrode material coating to 10-20 μm. After coating, dry it in an oven at 50-80 °C for 8-24 h. After drying, use a slicer to slice the area evenly coated with the slurry to obtain an electrode sheet.
10. The use of an alkaline ion battery negative electrode material according to claim 9, characterized in that: The conductive agent in S406 includes any one of super P and acetylene black, and the mass ratio of the binder, the conductive agent and the active powder is (1~1.5): (1~2): (6.5~8).
Citation Information
Cited By
Negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery
CN119601645A
Negative electrode material, preparation method thereof, negative electrode sheet and sodium ion battery
CN119601645B
Ammonium polyphosphate and MXene composite negative electrode material and preparation method and application thereof
CN122091553A